2005
DOI: 10.1111/j.1651-2227.2005.tb01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Host defence lectins in preterm neonates

Abstract: Aim: Deficiency in collectins is discussed as a risk factor for pulmonary and systemic infections in children and adults. The objective of this study was to determine serum concentrations of surfactant protein D (SP‐D) and mannose‐binding lectin (MBL) in preterm and term infants at birth. Methods: 47 preterm infants below 32 wk gestational age (GA) and 19 healthy, term newborn infants at birth have been included in the study, and SP‐D as well as MBL concentrations have been determined in umbilical cord blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
3
35
1
Order By: Relevance
“…In both series, median cord MBL concentrations were lower than in children and adults, consistent with a reported increase to adult levels during the first 3 months of postnatal life [21]. Perhaps surprisingly, we found no correlation between the MBL concentration in cord serum and gestational age (r ϭ 0.03; p ϭ 0.19); several independent groups have reported such a correlation [22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…In both series, median cord MBL concentrations were lower than in children and adults, consistent with a reported increase to adult levels during the first 3 months of postnatal life [21]. Perhaps surprisingly, we found no correlation between the MBL concentration in cord serum and gestational age (r ϭ 0.03; p ϭ 0.19); several independent groups have reported such a correlation [22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…Variation in MBL2 has been implicated directly in pre-term birth (Annells et al 2004(Annells et al , 2005 and low birth weight for women with recurrent spontaneous abortion (Kruse et al 2002; but see Baxter et al 2001). In the Kruse et al (2002) study, they associate MBL levels with preterm birth (see also Hilgendorff et al 2005) and could find no effect of paternal MBL2 genotype on outcome.…”
Section: Discussionmentioning
confidence: 94%
“…[35][36][37] Frakking et al 13 found that low MBL levels were associated with pneumonia in the first month of life in premature infants. Similarly, Hilgendorff et al 16 also suggested that low MBL levels might contribute to both pulmonary and systemic infection development in preterm infants. Our findings were in good agreement with these studies.…”
Section: Neonatal Comorbiditiesmentioning
confidence: 96%
“…16,28,32 Lau et al 32 studied MBL levels in 885 longitudinally collected serum samples from 168 preterm infants and 63 were genotyped for codon 54 mutation in MBL gene. They found that for infants with codon 54 mutation, there was a significant difference between preterm and term infants.…”
Section: Neonatal Comorbiditiesmentioning
confidence: 99%